Repeated supratherapeutic dosing of strontium ranelate over 15 days does not prolong QT(c) interval in healthy volunteers - Taubel, Jorg (Blackwell Publishing Ltd, 2012)
AIMS: The study was performed to assess the safety of strontium ranelate in accordance with the ICH, E14 guidelines for QT/QT(c) studies. Its primary objective was to compare supratherapeutic repeated dosing of strontium ranelate (4 g day(−1) for 15 days) with placebo on the largest time-matched mean QT(c) variation, from baseline to under treatment values, in healthy subjects. METHODS: Ninety-six healthy male and female subjects (27.7 ± 7.5 years) were included to receive 1 day of placebo followed by 15 days of supratherapeutic repeated dosing of strontium ranelate (4 g day(−1)), in a 4 month, randomized, placebo (16 days) and positive-controlled (single dose of moxifloxacin 400 mg preceded by 15 days of placebo), double-blind, double dummy, crossover design. Measurement of QT interval was performed automatically on the ECGs with subsequent manual onscreen over-reading by cardiologists using electronic callipers. RESULTS: The largest time-matched difference in QT(c)I (individual QT correction for heart rate) between moxifloxacin 400 mg and placebo was observed at 2 h post dose (mean [95% CI] 10.62 [7.90, 13.35] ms). For strontium ranelate (4 g day(−1)) the largest time-matched difference in QT(c)I compared with placebo was observed at 1 h post dose (mean [90% CI] 7.54 [5.17, 9.90] ms). No subject had a QT(c) greater than 480 ms during the study. Both moxifloxacin and strontium ranelate were well tolerated in healthy subjects. CONCLUSIONS: The findings of this study demonstrate that the administration of supratherapeutic repeated oral doses of strontium ranelate (4 g day(−1) for 15 days) does not lead to a prolongation of the QT/QT(c) interval above the threshold of regulatory concern.